2013
DOI: 10.1176/appi.ajp.2013.12060734
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Cognitive-Behavioral Therapy and Manualized Psychoeducation in the Treatment of Recurrent Depression: A Multicenter Prospective Randomized Controlled Trial

Abstract: The results indicate that maintenance CBT has significant effects on the prevention of relapse or recurrence only in patients with a high risk of depression recurrence. For patients with a moderate risk of recurrence, nonspecific effects and structured patient education may be equally effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(90 citation statements)
references
References 32 publications
6
75
1
5
Order By: Relevance
“…This study provides important evidence that MBCT-TS may confer ongoing protection for patients who would like an alternative to m-ADM. The results further suggest that psychosocial treatments, such as MBCT and CBT, 117,121,124 offer added value for patients who need them most, that is, those at highest risk of depressive relapse/recurrence. However, studies have tended to operationalise risk in somewhat different ways (e.g.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This study provides important evidence that MBCT-TS may confer ongoing protection for patients who would like an alternative to m-ADM. The results further suggest that psychosocial treatments, such as MBCT and CBT, 117,121,124 offer added value for patients who need them most, that is, those at highest risk of depressive relapse/recurrence. However, studies have tended to operationalise risk in somewhat different ways (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…Many patients with recurrent depression may have been on m-ADM for many years and for a variety of reasons would prefer to learn skills that they can use to stay well. The results further suggest that psychosocial treatments such as MBCT and CBT 117,121,124 offer added value for patients who need them most, that is, those at highest risk of depressive relapse/recurrence. The investment of effort by these patients in learning the skills taught in psychosocial treatments such as CBT and MBCT pays off.…”
Section: Implications For Practicementioning
confidence: 82%
See 1 more Smart Citation
“…In a more recent, prospective, randomized, observer blinded multicenter study Stangier and colleagues compared the rates of relapse in 180 completely remitted depressed patients with three or more previous episodes who either received TAU plus Maintenance Cognitive Therapy (MCT) or TAU plus Manualized Psychoeducation (MAPE) for eight months [53]. Afterwards the patients were followed up for one year.…”
Section: Findings Concerning More "Severe and Complicated Patients"mentioning
confidence: 99%
“…), don't have enough personal effectiveness, can be trained to trust their ability to succeed more, strengthen their selfworth, and the possibility of being successful (9). Several studies have shown that educational programs for pa- tients based on self-training can be an effective strategy to improve knowledge, skills, self-efficacy, and repairing behaviors associated with the disease to help contribute in their treatment (10,11). Sadeghi SenaAbadi also pointed in his study that self-care education is effective on patients with stoma (12).…”
Section: Introductionmentioning
confidence: 99%